Effect of Diazepam on Severity of Acute Pancreatitis: Possible Involvement of Peripheral Benzodiazepine Receptors. (17th July 2013) - Abed, Alireza; Minaiyan, Mohsen; Safaei, Azadeh; Taheri, Diana
Abstract : Acute pancreatitis is a lethal inflammatory condition of pancreas with high mortality rate. There is a pressing need for research to explore active agents and novel mechanisms involving in the treatment of pancreatitis. Clinical studies have shown after the initial acinar cell injury plasma levels of pro-inflammatory cytokines are elevated in patients with acute pancreatitis and the degree of cytokine elevation correlates with disease severity. Diazepam may decrease interleukin release from macrophages, suppress neutrophil activities, and exhibit anti-inflammatory effects. So it is expected that in vivo pretreatment of acute pancreatitis with different doses of diazepam can attenuate its severity. Thus, we evaluated the effects of diazepam, intraperitoneally (5, 10, and 20 mg/kg i.p.), intracerebroventricularly (ICV 10  μ g), and concurrently with flumazenil (1 mg/kg) on cerulein-induced acute pancreatitis in mice. Interestingly, the pretreatment with diazepam (5 mg/kg i.p.) reduced significantly the inflammatory response of acute pancreatitis by ameliorating pancreatic edema, amylase and lipase serum levels, myeloperoxidase activity, pancreatic TNF-alpha, and pathological alteration compared to control group. Diazepam i.c.v. was ineffective, suggesting that central benzodiazepine receptors have no significant role in this property. These results demonstrate that pretreatment with diazepam exhibits anti-inflammatory property in cerulein-induced acute pancreatitis possibly through peripheral benzodiazepine receptors.